2020
DOI: 10.1002/emp2.12145
|View full text |Cite
|
Sign up to set email alerts
|

Patient factors associated with SARS‐CoV‐2 in an admitted emergency department population

Abstract: Background The SARS‐CoV‐2 (COVID‐19) virus has wide community spread. The aim of this study was to describe patient characteristics and to identify factors associated with COVID‐19 among emergency department (ED) patients under investigation for COVID‐19 who were admitted to the hospital. Methods This was a retrospective observational study from 8 EDs within a 9‐hospital health system. Patients with COVID‐19 testing around the time of hospital admission were included. The primary outcome measure was COVID‐19 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Anecdotal case reports suggest that patients with dual diagnosis have a higher risk of progression to severe forms of COVID-19 [ 84 ]. However, some studies did not find any association between alcohol use and COVID-19 risk or severity [ 85 , 86 ]. Contrarily, a Chinese case control study, observed that low dose of alcohol intake is associated with lower risk of COVID-19 morbidity [ 87 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…Anecdotal case reports suggest that patients with dual diagnosis have a higher risk of progression to severe forms of COVID-19 [ 84 ]. However, some studies did not find any association between alcohol use and COVID-19 risk or severity [ 85 , 86 ]. Contrarily, a Chinese case control study, observed that low dose of alcohol intake is associated with lower risk of COVID-19 morbidity [ 87 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…Although the COVID-19 pandemic has prompted innovations in the care and treatment of persons who use substances [ 31 ], continued surveillance is urgently needed to examine trends in substance use patterns during the pandemic. Published research in the past year discussed the rising prevalence of substance use around the world [ 3 ▪ , 4 ▪ , 6 ▪ , 7 ▪▪ , 8 ▪ ] and suggested that individuals who use substances may be at an increased risk for COVID-19 [ 32 ▪ , 33 ▪▪ ]. Implementation of stay-at-home orders were associated with increased overdose rates [ 19 ▪ 21 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these changes in substance use patterns internationally, conflicting evidence is present regarding associations between COVID-19 positivity and substance use. A retrospective study of emergency department admissions who underwent COVID-19 testing found that the odds of a patient testing positive for coronavirus was lower if they had a history of using alcohol or other substances in a way, which may cause harm [ 32 ▪ ]. However, electronic health record data gathered from more than 350 hospitals in the United States suggested that a past-year substance use disorder diagnosis significantly increased the likelihood that a patient would be diagnosed with COVID-19 [ 33 ▪▪ ].…”
Section: Coronavirus Disease-related Outcomesmentioning
confidence: 99%
“…This brief commentary is intended to accompany the journal's podcast on several articles. [1][2][3][4][5][6][7][8][9] The 2019 novel coronavirus (COVID-19) has occupied most of our personal and professional lives this year. This August edition of the journal has 9 contributions about the pandemic and our colleagues' Collectively, the 9 articles in the August edition of JACEP Open provide a broad description of both the COVID epidemiology and the health care response.…”
mentioning
confidence: 99%
“…They created a specific COVID aircraft, modified their call taking and response processes, emphasized more aggressive airway management in flight, and instituted specific decontamination steps to maximize crew safety while keeping the aircraft in service as much as possible. Morris et al 8 describe the first outbreak in the United States in a King County, Washington, skilled nursing facility in “Lessons Learned From COVID‐19 Outbreak in a Skilled Nursing Facility, Washington State.” They discuss lessons learned and the importance of improving communication between EMS and skilled nursing facilities, including skilled nursing facilities in regional disaster planning, load balancing COVID patients between multiple hospitals, and separation of those patients and staff with COVID into distinct wings to decrease viral spread within the facility.…”
mentioning
confidence: 99%